Evaluation of Menthol-Based Hydrophobic Deep Eutectic Solvents for the Extraction of Bisphenol A from Environment Water. (13th June 2021) - An, Yena; Row, Kyung Ho
Abstract: Deep eutectic solvents (DES) which possess hydrophobicity were synthesized from various carboxylic acid or fatty acids and menthol to remove bisphenol A, a micropollutant present in water-based environments, via liquid–liquid extraction. The bisphenol A concentration was measured quantitatively by ultraviolet-visible spectroscopy. The structure and properties of the DES were examined by Fourier transform infrared spectroscopy and 1 H nuclear magnetic resonance spectroscopy, and the interaction of the cephalic compound was investigated. The menthol–propionic acid and menthol–formic acid DES provided the satisfactory extraction performance and several parameters, including the type and volume, stirring speed, and time of the extraction procedure, were optimized. Excellent recovery rates of 98.2%–99.0% for bisphenol A were obtained under the optimized conditions.